Diet of Asian Glossy Starling (Aplonis panayensis) in Kuching City - Nursyafiqah, Shazali; Mohd. Azlan Jayasilan, bin Abdul; Gulam, Azad; Andrew Alek, Tuen (Universiti Malaysia Sarawak, (UNIMAS), 2014)
The objectives of this study are to determine the diet of AGS in Kuching City, Sarawak, to determine the frequency of occurrence of fruits and insects in the diet of starlings, and to determine whether their diet compositions depend on the availability of fruits and insect in the vacinity of area of study.